2020
DOI: 10.1007/s00382-020-05466-1
|View full text |Cite
|
Sign up to set email alerts
|

Kilometer-scale modeling projects a tripling of Alaskan convective storms in future climate

Abstract: Convective storms produce heavier downpours and become more intense with climate change. Such changes could be even amplified in high-latitudes since the Arctic is warming faster than any other region in the world and subsequently moistening. However, little attention has been paid to the impact of global warming on intense thunderstorms in high latitude continental regions, where they can produce flash flooding or ignite wildfires. We use a model with kilometer-scale grid spacing to simulate Alaska’s climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…We know from observations that organized convective systems are present but rare in the pan-Arctic [Жукова et al, 2018, Punkka andBister, 2015]. In a predecessor study [Poujol et al, 2020] we showed that organized convective storms are projected to triple by the end of the century in Alaska under a high emission scenario as a result of anthropogenic climate change. These results are supported by observational studies in Siberia [Chernokulsky et al, 2011] that report a strong increase in the frequency of deep convective clouds during the period 1991-2010.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…We know from observations that organized convective systems are present but rare in the pan-Arctic [Жукова et al, 2018, Punkka andBister, 2015]. In a predecessor study [Poujol et al, 2020] we showed that organized convective storms are projected to triple by the end of the century in Alaska under a high emission scenario as a result of anthropogenic climate change. These results are supported by observational studies in Siberia [Chernokulsky et al, 2011] that report a strong increase in the frequency of deep convective clouds during the period 1991-2010.…”
mentioning
confidence: 81%
“…We are interested in convective storms in the Interior, Western and Northern Alaska. As in [Poujol et al, 2020], we define continental Alaska as the five climate regions shown in Figure 1a, which were defined by [Bieniek et al, 2012]. The North Slope has an Arctic climate and convective storms are rarely observed in this region [Grice and Comiskey, 1976].…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations